Improving the efficacy of carbon tax policies - Elie Appelbaum (Journal of Government and Economics (JGE), 2021)
This paper examines the efficacy of carbon tax policies in view of the interactions between such policies and the firm's carbon efficiency and financing decisions. We show that because the government, unlike capital markets, does not price its policy's risk by taking into account default probabilities, the firm takes advantage of the government by using senior debt to minimize the carbon tax policy's cost. The shift to debt financing, in turn, mitigates the carbon tax policy's efficacy, resulting in lower carbon efficiency, thus higher carbon emissions. To remedy the government's predicament, we propose a correct-pricing rule that mimics market equilibrium conditions, thereby forcing firms to consider government interests. Such a rule renders senior debt no longer useful for reducing the carbon tax policy's cost. As a result, the tax policy's efficacy increases, hence reducing carbon emissions. Finally, we briefly consider and comment on the case of a social-welfare maximizing government that strategically chooses its carbon tax.
Keywords: H20; H21; H25; G32; G33; G38; Q50; 330; Carbon taxes; Government policy; Capital structure; Stakeholders; Bankruptcy